Book review: Matematik for lærerstuderende. Delta: fagdidaktik - Ryve, Andreas (NOMAD Nordic Studies in Mathematics Education, 2009)
Jeppe Skott, Hans Christian Hansen og Kristine Jess (2008). Matematik for lærerstuderende. Delta: fagdidaktik. Samfundslitteratur, Frederiksberg. ISBN 978-87-593-1340-4